Get to Know More about Fetishism and Strategies Intervention to Increase Quality of Life for Individuals with Fetishistic Disorders - Nur Fatwikiningsih; Wahyu Utami; Mentari Marwa; Dyah Mustika Kusuma Winahyu (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Fetishism is mostly found in men and not seen in clinical conditions. The number of the victim is few, harmless to the victims, and not dangerous. Many individuals are comfortable with their fetishism and may only seek treatment because of legal or interpersonal pressure. Many studies reported individual with fetishism may experience feelings of guilt, shame, low self esteem, and depression to hide their activities. Individuals with fetishistic disorders need helping to increase their quality of life and how to decrease stigma on a person with fetishistic disorder and fetishistic behavior. The purpose study of literature will review the clinical features of fetishistic disorder, causes fetishistic behaviours, management intervention and support for a person with fetishistic disorders to increase their quality of life. Diagnostic and Statistical Manual of Mental Disorders-5 suggests making a clear distinction between fetishism (fetishistic behavior) and fetishistic disorder. Fetishistic disorders deﬁned as fantasies, sexual urges and behaviours which cause signiﬁcant distress or impairment in social, occupational or other important areas of function. Fetishism may be related to specific body parts (hair, foot), non-living objects (pantyhose, baby diapers, bra, silk stockings, silk petticoat, rubber teat, body parts, leather garments, catheters, silk handkerchiefs), and behaviors (wearing, caressing, stacking, insertion into the rectum, friction, suction, stealing). Various explanations causes fetishistic behaviours and fetishistic disorder including biological, sociocultural, behavioural, psychoanalysis, and cognitive theories. Intervention for future directions will be offered can include behavioural, psychoanalytic, cognitive strategies.